The Construction of Public Space through Language - Juanzo, Carlo Joseph M. (International Journal of Linguistics and Translation Studies, 2022)
Among countries have all had an impact on how language is regarded. When considering the linguistic landscape in the modern time of scientific-linguistic studies, multilingualism, various discursive acts, sociolinguistic frames and affordances all complicate the process of viewing and placing it. In small-scale research of Odiongan, a municipality of Tablas Island, a rapidly rising administrative and commercial centre in Romblon, visual analyses of discourses, as indicated by the linguistic landscape, were done. In addition, the study summarizes some of the studies that have dealt with the linguistic landscape. It also outlines the theoretical framework that was employed in the current investigation and presents the question that this study seeks to solve. Among the organizations that have been selected as the study's specific resources are a community-governmental office, which represents a government body, a state university, which represents the educational sector, and a church, which represents a religious entity. The public signs chosen to reflect the linguistic landscape practiced in these societal components were also chosen to represent the linguistic landscape practiced in each of the institutions studied.